Potentially Inappropriate Prescriptions of Antipsychotics for Patients With Dementia - Machado-Duque, Manuel Enrique; Valladales-Restrepo, Luis Fernando; Ospina-Cano, Juan Alberto; Londoño-Serna, María José; Machado-Alba, Jorge Enrique (Frontiers in Pharmacology, 2021)
Dementias are neurodegenerative and progressive diseases of the central nervous system. The objective of this study was to determine the frequency of potentially inappropriate prescriptions of antipsychotics in a group of patients diagnosed with dementia in Colombia. This was a cross-sectional study based on a population database for drug dispensing that identified prescriptions of antidementia drugs, antipsychotics, and other drugs for patients with a diagnosis of dementia. Descriptive statistics and bivariate and multivariate analyses were performed. A total of 11372 patients with dementia were identified; 66.6% were women, and the mean age was 80.5±9.6 years. Alzheimer's disease was the most frequent diagnosis (76.6%). A total of 69.0% of patients received antidementia drugs. A total of 37.1% of patients received some antipsychotic, especially atypical antipsychotics (31.0%). Increased age, being treated with memantine, simultaneously presenting with anxiety, depression, and psychotic disorders, and concomitantly receiving anticonvulsants, bronchodilators and benzodiazepines were associated with a greater probability of being prescribed antipsychotics. More than one-third of patients with dementia received antipsychotic prescriptions, which are considered potentially inappropriate because they can worsen cognitive decline and favor the occurrence of adverse events.